Assessing the Flexibility of the Proximal Thoracic Segments Above the "Potential Upper Instrumented Vertebra" Using the Cervical Supine Side Bending Radiographs in Lenke 1 and 2 Curves for Adolescent Idiopathic Scoliosis Patients. Issue 16 (15th August 2016) - Chan, Chris Yin Wei; Chiu, Chee Kidd; Kwan, Mun Keong
Abstract : Study Design: A prospective study. Objective: The aim of this study was to analyze the proximal thoracic (PT) flexibility and its compensatory ability above the "potential UIV." Summary of Background Data: Shoulder and neck imbalance can be caused by overcorrection of the main thoracic (MT) curve due to inability of PT segment to compensate. Methods: Cervical supine side bending (CSB) radiographs of 100 Lenke 1 and 2 patients were studied. We further stratified Lenke 1 curves into Lenke 1−ve: PT side bending (PTSB) < 15° ( n = 33) and Lenke 1+ve: PTSB 15° to 24.9° ( n = 37). The right side bending (RSB) and left side bending (LSB) angles were measured (T1–T6). Compensatory ability of the PT segment was analyzed with assumption of a "horizontal UIV" position. Results: From T1 to T6 vertebrae, the RSB angle values showed increasing positive values. The LSB angle, comparing Lenke 1−ve versus 2 and Lenke 1+ve versus 2, showed significant difference at T2 to T6. The LSB angle comparing Lenke 1−ve versus 1+ve achieved significant difference at T5 and T6. In Lenke 2 curves, >80.0% of cases of the PT segment were unable to compensate at T3-T6. In Lenke 1+ve curves, 78.4% were unable to compensate at T6, followed by T5 (75.7%), T4 (73.0%), T3 (59.5%), T2 (27.0%), and T1 (21.6%). In Lenke 1-ve curves, 36.4% of cases were unable to compensate at T6, followed by T5 (45.5%), T4 (45.5%), T3 (30.3%), T2 (21.2%), and T1 (15.2%). A significant difference between Lenke 1−ve and Lenke 1+ve was observed from T3 to T6. The difference between Lenke 1+ve and Lenke 2 curves was significant only at T2. Conclusion: The compensation ability and the flexibility of the PT segments of Lenke 1−ve and Lenke 1+ve curves were different. Lenke 1+ve curves demonstrated similar characteristics to Lenke 2 curves. Level of Evidence: 3